Developing Secondary School Students' Sustainable Living Awareness to Help Achieve the Sustainable Development Goals - Koculu, Asli (MDPI, 2025)
In today's world, there are numerous challenges all over the world because of human lifestyles. Therefore, raising awareness of sustainable living is crucial to developing ways for everyone to live better while meeting both present and future generations' environmental, social, and economic needs. In this context, the aim of the current research was to investigate the effects of the learn-think-act-based Education for Sustainable Development Goals (ESDG) program on secondary school students' sustainable living awareness. A single-group pre- and post-test model was used in this research. The research group consisted of 34 seventh-grade students enrolled in the Environmental Education and Climate Change elective course at a public school in Istanbul, T & uuml;rkiye. The data were collected using the Sustainable Living Awareness Scale (SLAS). A paired-sample test was used for data analysis. The findings show that there were statistically significant differences between the pre- and post-test total and sub-factor scores of the secondary school students' sustainable living awareness, with the post-test scores being higher. In other words, the results show that learn-think-act-based ESDG can be an effective way to develop students' sustainable living awareness.
Keywords: sustainable living awareness; Sustainable Development Goals; Education for Sustainable Development Goals; secondary school students; LIFE-STYLES; EDUCATION; COMPETENCE; IMPACT; ESD; Science & Technology - Other Topics; Environmental Sciences & Ecology